Patterns, drivers, and a predictive model of dam removal cost in the United States - Duda, Jeffrey J.; Jumani, Suman; Wieferich, Daniel J.; Tullos, Desiree; McKay, S. Kyle; Randle, Timothy J.; Jansen, Alvin; Bailey, Susan; Jensen, Benjamin L.; Johnson, Rachelle C.; Wagner, Ella; Richards, Kyla; et al. (Frontiers in Ecology and Evolution, 2023)
Given the burgeoning dam removal movement and the large number of dams approaching obsolescence in the United States, cost estimating data and tools are needed for dam removal prioritization, planning, and execution. We used the list of removed dams compiled by American Rivers to search for publicly available reported costs for dam removal projects. Total cost information could include component costs related to project planning, dam deconstruction, monitoring, and several categories of mitigation activities. We compiled reported costs from 455 unique sources for 668 dams removed in the United States from 1965 to 2020.